Influence of thickness and degree of opacity of lithium disilicate on the degree of conversion and bond strength of resin cements - Queiroz, Mariana Elias [UNESP]; Maluly-Proni, Ana Teresa [UNESP]; Tsutsumi, Mariana Sati Cantalejo [UNESP]; Dallazen, Eduardo [UNESP]; de Castro-Hoshino, Lidiane Vizioli; de Souza, Monique; Baesso, Mauro Luciano; dos Santos, Paulo Henrique [UNESP] (Elsevier, 2023)
The aim of this study was to evaluate the influence of various opacities and thicknesses of lithium disilicate on the degree of conversion (DC) of two resin cements and on their bond strength (BS) to the ceramic. Two hundred and forty ceramic samples of lithium disilicate with high translucency (HT), low translucency (LT), and medium opacity (MO) were obtained from IPS e. max CAD in five different thicknesses. Light-cured and dual-cured resin cements were used for DC (n = 9) and BS (n = 8). Cement samples were light-cured under ceramic samples and analyzed using a Raman confocal spectrometer to determine the DC. For BS, resin cement cylinders were fabricated using ceramic samples which were thsen subjected to a microshear bond strength test. The mean values were provided for statistical analysis. The increase in thickness resulted in a decrease in DC for both cements under all experimental conditions, but only affected the BS of the light-cured cement for the MO ceramic. Comparing the opacities, the most translucent ceramics with particular thicknesses exhibited higher DC values than the less translucent ceramics. The LT and MO ceramics with certain thicknesses exhibited the highest BS values than the HT. The dual-cured cement generally showed highest values in both analyses than the light-cured cement. A thicker and more opaque ceramic material can reduce the DC of the cement. The BS decreases with the increasing thickness of the more-opaque ceramics.
Keywords: Dental materials; Dental porcelain; Polymerization; Resin cement